2013
DOI: 10.1016/j.ajpath.2013.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Impairs Atherosclerosis Regression in Mice

Abstract: Diabetic patients are known to be more susceptible to atherosclerosis and its associated cardiovascular complications. However, the effects of hyperglycemia on atherosclerosis regression remain unclear. We hypothesized that hyperglycemia impairs atherosclerosis regression by modulating the biological function of lesional macrophages. HypoE (Apoe(h/h)Mx1-Cre) mice express low levels of apolipoprotein E (apoE) and develop atherosclerosis when fed a high-fat diet. Atherosclerosis regression occurs in these mice u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
0
13
1
Order By: Relevance
“…However, calculating the percentage change in the regression groups versus their respective baseline groups showed that both reduction in lesion size and CD68+ areas were significantly less alleviated in HDAd-LDLR treated STZ-diabetic mice compared to the non-diabetic mice (51% lesion size reduction in non-diabetic mice vs. 36% in STZ-diabetic mice, and reduction of 77% CD68+ cells in non-diabetic mice vs. 57% in STZ-diabetic mice), consistent with our previous study [ 8 ]. Using hypomorphic ApoE mice, Gaudreault et al also reported an impaired lesion size reduction with STZ-diabetes, but in contrast to our past and present results, no differences were noted in the cell composition of the atherosclerotic lesion [ 42 ]. Besides the use of different regression models, this difference might be due to different changes in lipoprotein composition (more VLDL-cholesterol reduction) and degree of cholesterol reduction, with HDAd-LDLR treatment being more effective.…”
Section: Discussioncontrasting
confidence: 99%
“…However, calculating the percentage change in the regression groups versus their respective baseline groups showed that both reduction in lesion size and CD68+ areas were significantly less alleviated in HDAd-LDLR treated STZ-diabetic mice compared to the non-diabetic mice (51% lesion size reduction in non-diabetic mice vs. 36% in STZ-diabetic mice, and reduction of 77% CD68+ cells in non-diabetic mice vs. 57% in STZ-diabetic mice), consistent with our previous study [ 8 ]. Using hypomorphic ApoE mice, Gaudreault et al also reported an impaired lesion size reduction with STZ-diabetes, but in contrast to our past and present results, no differences were noted in the cell composition of the atherosclerotic lesion [ 42 ]. Besides the use of different regression models, this difference might be due to different changes in lipoprotein composition (more VLDL-cholesterol reduction) and degree of cholesterol reduction, with HDAd-LDLR treatment being more effective.…”
Section: Discussioncontrasting
confidence: 99%
“…Numerous studies have reported changes in circulating microRNA levels associated with accelerated atherosclerotic disease in diabetes ( de Candia et al., 2017 ; Zampetaki et al., 2010 ). As we and others ( Gaudreault et al., 2013 ; Nagareddy et al., 2013 ) observed that myeloid cells are impacted by hyperglycemia, we performed microRNA sequencing on Ly-6C hi monocytes and macrophages isolated from mouse models of hyperglycemia that included the STZ-induced and spontaneous Akita mouse models of diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…Cardiovascular disease (CVD) and diabetes are both associated with leukocytosis (1,2). We and others have previously reported that hyperglycemia in mice impaired the resolution of atherosclerosis after lipid lowering (3,4). Hyperglycemia also stimulated myelopoiesis in the mice, which increased circulating levels of monocytes and neutrophils and their entry into atherosclerotic plaques (5)(6)(7).…”
Section: Introductionmentioning
confidence: 96%